Pengaruh Penambahan Tepung Rumput Laut terhadap Daya Terima Nasi IR 64 - Fauzi, Fa'izah; Alsuhendra, Alsuhendra; Efrina, Efrina (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2023)
IR 64 rice in Indonesia are among the highest sold, with a percentage of 26.09% while IR 42 rice was 10%, Muncul rice was 8.24% and Setra Ramos rice at 5.94%. However, white rice has a low fibre content. This research was conducted to determine the effect of adding seaweed flour (Eucheuma spinosum) on consumer acceptance of IR 64-cooked rice. The aspects studied were rice's taste, colour, aroma, and texture. This research started with making seaweed flour, which added 0.5% CaO as a bleaching agent during the soaking process. Then the seaweed flour was added to the rice before cooking at different contents of 5, 6, and 7%. Furthermore, the rice is cooked using Liwet technique. This rice was then tested organoleptically with four expert panelists (Culinary Education lecturers) and 30 semi-trained panelists (students of the Pendidikan Tata Boga Program, Universitas Negeri Jakarta). Based on the results of the Friedman test, with a confidence level of 95%, it shows that there is no influence on the aspects of aroma, texture, and colour, but there is an influence on the aspects of taste. Tukey's test results with α= 0.05 showed a tendency for liking the addition of 6% flour. According to 4 expert panelists, adding 6% has the characteristic taste of rice that is almost strong; the colour is close to the original white rice. The aroma of seaweed is barely prominent and has an almost fluffier texture.